2009
DOI: 10.1055/s-0029-1185440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seven Tricyclic Diterpenoids from Needles ofTaxus mediavar.Hicksiion Stimulus-Induced Superoxide Generation, Tyrosyl or Serine/Threonine Phosphorylation and Translocation of Cytosolic Compounds to the Cell Membrane in Human Neutrophils

Abstract: Taxol has been widely used as an anticancer drug for ovarian, breast, lung and prostate cancer. Some kinds of Taxus plants are widely distributed in the Northeast Asia region. We have isolated seven tricyclic diterpenoids, taxinine, taxagifine, 5-O-cinnamoyltaxacin I triacetate, 5-decinnamoyltaxinine J, 5-cinnamoyl-9-acetyltaxicin I, taxacin and taxol from the needles of Taxus media var. Hicksii, and investigated their effects on stimulus-induced superoxide generation and translocation of cytosolic compounds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Recently, it was reported that taxinine together with another six tricyclic diterpenoids suppress superoxide generation mainly via suppressing tyrosine or serine/threonine phosphorylation, and the translocation of cytosolic compounds to the cell membrane in human neutrophils. In addition, when concentration reached to the dosage suppressing superoxide generation needed, these compounds showed no effect of hemolysis …”
Section: Taxanes Isolated From Yew Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that taxinine together with another six tricyclic diterpenoids suppress superoxide generation mainly via suppressing tyrosine or serine/threonine phosphorylation, and the translocation of cytosolic compounds to the cell membrane in human neutrophils. In addition, when concentration reached to the dosage suppressing superoxide generation needed, these compounds showed no effect of hemolysis …”
Section: Taxanes Isolated From Yew Treesmentioning
confidence: 99%
“…In addition, when concentration reached to the dosage suppressing superoxide generation needed, these compounds showed no effect of hemolysis. 46 4.3. 6/8/6-Taxanes 3: Basic Taxa-4(20),11-dienes (Table 4 and Figure 10)…”
Section: Taxanes Isolated From Yew Treesmentioning
confidence: 99%
“…It was reported previously that some triterpenoids Yagi-Chaves et al, 2006;He et al, 2008) and tricyclic diterpenoids (Tong et al, 2009) suppressed tyrosyl or serine/threonine phosphorylation of proteins and translocation to the plasma membrane of p47 phox , p67 phox and rac in parallel to the effect of stimulus-induced superoxide generation. The present study investigated the effects of five secoiridoids isolated from the root of G. straminea on superoxide generation, tyrosyl or serine/threonine phosphorylation of proteins and the translocation of cytosolic compounds, p47 phox , p67 phox and rac to the plasma membrane in human neutrophils and antioxidant activity.…”
Section: Introductionmentioning
confidence: 86%
“…It was reported previously that some triterpenoids (Chen et al , ; Yagi‐Chaves et al , ; He et al , ) and tricyclic diterpenoids (Tong et al , ) suppressed tyrosyl or serine/threonine phosphorylation of proteins and translocation to the plasma membrane of p47 phox , p67 phox and rac in parallel to the effect of stimulus‐induced superoxide generation. The present study investigated the effects of five secoiridoids isolated from the root of G .…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that tricyclic diterpenoid compounds isolated from T. media suppressed stimulus-induced superoxide generation in human neutrophils [9]. However, the corresponding research on bioflavonoids from T. media have not been reported.…”
Section: Introductionmentioning
confidence: 94%